Pemberdayaan Masyarakat Desa Melalui Literasi Keuangan Syariah dan Pengenalan Produk Bank Syariah di Desa Perkebunan Gunung Melayu - Pinasti Sri Guntari; Salma Nasution (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
This study aims to analyze and implement the Village Community Empowerment Program through Sharia Financial Literacy and Introduction to Sharia Banking Products in Perkebunan Gunung Melayu Village. This program is motivated by the low level of formal financial literacy, particularly regarding Sharia banking, among the village community. The methods used are outreach and mentoring, focusing on two main pillars: instilling wise money management habits and introducing Sharia banking services. The results of the activities indicate an increase in community awareness of the importance of saving as a foundation for wise money management from an early age. Participants learn to manage expenses, distinguish between needs and wants, and prepare funds for the future, which are habits that form the basis for healthy and responsible financial behavior. In addition, the community is provided with a comprehensive understanding of the various financial services provided by Sharia banks, such as savings, deposits, checking accounts, ATM cards, and digital services. This understanding empowers the community to manage their money and conduct transactions safely and efficiently through a formal banking system that complies with Sharia principles. Overall, this program contributes significantly to increasing Sharia financial inclusion and literacy in Perkebunan Gunung Melayu Village.